PENDAMPINGAN REBRANDING DAN DIGITAL MARKETING SEBAGAI STRATEGI PEMASARAN PRODUK VIRGIN COCONUT OIL (VCO) PADA UMKM BERIUK MAJU DUSUN MENTIGI, DESA MALAKA - Khaerullah, Nurman; Putri, Arin Rizki; Polanunu, Mochamad Boyke Putra; Rizki, Citra Aulia; Lestari, Andi Tri (Jurnal Pepadu, 2024)
Beriuk Maju MSME is one of the MSMEs in Mentigi Hamlet, Malaka Village, Pemenang Sub-district, North Lombok Regency. This MSME is managed by women and people with disabilities. The production and marketing of MSME Beriuk Maju is currently not developed enough and produces significant sales due to the many challenges and lack of knowledge about marketing strategies. So it is necessary to provide rebranding and digital marketing assistance so that Virgin Coconut Oil (VCO) products can attract consumers and reach a wider market. This assistance was carried out for one month by Mataram University KKN-PMD students. This mentoring method begins with surveis and observations of MSMEs, Re-Branding of MSME product packaging, and sales promotion through social media (digital marketing). This assistance produces product designs for packaging and Instagram social media for promotion. From this assistance, it is concluded that product rebranding is very important to produce products that attract buyers and promotions carried out through social media can reach a wider market to increase sales.